Multiparametric MRI for the Diagnosis of Tumor Type in Patients Suspicious of Inner Gland Prostate Cancer - Ghane, Zahra; Faeghi, Fariborz; Ghafoori, Mahyar; Payandeh, Abolfazl (Urology Journal, 2019)
Purpose: The current study aimed to evaluate multiparametric MRI for the diagnosis of type of tumor (benign or malignant) in patients suspicious of inner gland prostate cancer. Materials and Methods: This cross-sectional study was conducted on 44 consecutive patients with a clinical impression of prostate cancer who were referred to the MRI department of Payambaran Hospital, Tehran, Iran for confirmative diagnostic evaluation. Cases suspected of tumor relapse and those who previously underwent treatment for prostate cancer were excluded. Multiparametric MRI was performed for every patient by using a 1.5 Tesla device with an integrated endorectal and pelvic-phased array coil. All patients subsequently underwent MRItransrectal ultrasound fusion biopsy. The diagnostic value of each sequence was then investigated individually and in combination with other techniques by comparing the results with histological findings from MRI–TRUS fusion biopsy. Results: Among the techniques, T2-weighted imaging (T2W) had the highest sensitivity and specificity while dynamic contrast enhanced (DCE) technique had the least. Diffusion-weighted imaging (DWI) and magnetic resonance spectroscopy (MRS) had a similar sensitivity and specificity and did not significantly differ from T2W. Adding functional techniques to T2W did not improve diagnostic indices compared to T2W alone. Quantitative evaluation of apparent diffusion coefficient (ADC), DWI, and MRS showed that all techniques were able to differentiate between benign and malignant tumors. However, the quantitative combination of these sequences decreased diagnostic performance. Conclusion: T2W is the best technique for the diagnosis of type of tumor in terms of benignancy or malignancy in patients suspicious of inner gland prostate cancer. Adding functional imaging measurements to T2W does not improve its diagnostic value.